Role of Bone Marrow Trephine Biopsies in the Diagnosis of Hematological and Non-Hematological Disorders - Pande, Kricha; Sinha, Arvind Kumar; Pradhan, Anju; Rijal, Suman; Bhatta, Nisha Keshari (Nepalese Medical Journal, 2020)
Introduction: Bone marrow examination has become increasingly important for the diagnosis and treatment of hematologic and other illnesses. Bone marrow aspirates along with their peripheral smears and bone marrow trephine biopsies are considered to be complementary. Materials and Methods: This hospital-based, cross-sectional study was carried out in the Department of Pathology for one year (March 2011 to March 2012) at BPKIHS, Dharan. Fortyeight adequate bone marrow aspirates along with peripheral blood smears and trephine biopsies were selected and examined. Bone marrow trephine biopsies performed simultaneously with aspirate were correlated with the other two fi ndings to arrive at a conclusive diagnosis. Results: Bone marrow aspiration and trephine biopsy were found as complementary tests in 51.8% of cases. Bone marrow trephine biopsy provided a conclusive diagnosis in 25.9% of cases where bone marrow aspiration was inconclusive. Bone marrow aspiration alone was diagnostic in 22.2% of cases. In 43.7% of cases both aspiration and trephine biopsy were unable to provide a specificdiagnosis. Bone marrow biopsy was the diagnostic investigation in cases like aplastic anemia, myelofi brosis, and hypoplastic marrow. Conclusions: This study concludes that bone marrow aspiration smear along with peripheral smear findings and marrow trephine biopsy is required to arrive at a conclusive result.